40ar/39ar dating of paleoproterozoic shear zones in the ellesmere–devon crystalline terrane, nunavut, canadian arctic - Caswell, Brandon; Gilotti, Jane A.; Webb, Laura E.; McClelland, William C.; Kośmińska, Karolina; Piepjohn, Karsten; von Gosen, Werner (Canadian Journal of Earth Sciences, 2021)
Paleoproterozoic gneisses of the Ellesmere–Devon crystalline terrane on southeastern Ellesmere Island are deformed by metre-scale, east-striking mylonite zones. The shear zones commonly offset pegmatitic dikes and represent the last episode of ductile deformation. Samples were dated by the40 Ar/39 Ar step-heating method to put an upper limit on the time of deformation. Biotite from one tonalitic protolith and five shear zones give geologically meaningful results. Clusters of unoriented biotite grains pseudomorph granulite-facies orthopyroxene in some of the weakly deformed gneisses, whereas the shape-preferred orientation of biotite defines the mylonitic fabric. The intrusive age of the tonalitic protolith is 1958 6 12 Ma, based on previous U–Pb dating of zircon.40 Ar/39 Ar analysis of biotite from the same sample gave a plateau age of 1929 6 23 Ma, which is interpreted as cooling from regional granulite facies metamorphism. Three nearby samples of mylonitic tonalite have40 Ar/39 Ar ages in the range of 1870–1840 Ma. Biotite from two granitic mylonites over 80 km away return high-resolution Ar spectra in the same range, implying that widespread ductile shearing occurred at 1870– 1840 Ma, or 90 million years after cooling from regional metamorphism. Although the 2.0–1.9 Ga gneisses of southeastern Ellesmere Island correlate with the Inglefield Mobile Belt in North-West Greenland and the Thelon Tectonic Zone, the late shear zones are superimposed on that juvenile arc long after the 1.97 Ga Thelon orogeny.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Biotite; Ellesmere Island; Mylonite; Shear zone